The last kids on Earth and the midnight blade - Brallier, Max; Holgate, Douglas (New York : Viking, an imprint of Penguin Random House, 2019)
Surviving their first winter after the Monster Apocalypse was no easy feat, yet Jack and his buddies waste no time springing to action against some of the nastiest, most evil monsters around. When Jack discovers his Louisville Slicer has new, otherworldly powers, he's thrown into epic training to find out what kind of destruction the blade can wield. But between fighting off zombies, fleeing from strange, glowy Vine-Thingies erupting from the ground, and squeezing in a video game session or two, there's barely time left to figure out what's wrong with their buddy, Dirk, who's been acting weird any time he's around the undead. When an unexpected villain appears, can Jack and his friends save themselves--and the rest of the world--from cosmic domination?
"Netflix. A Netflix original series"--Cover.
"Barnes & Noble exclusive edition includes bonus material."
Keywords: Monsters -- Juvenile fiction; Zombies -- Juvenile fiction; Supervillains -- Juvenile fiction; Weapons -- Juvenile fiction; Survival -- Juvenile fiction; Monsters -- Fiction; Zombies -- Fiction; Supervillains -- Fiction; Weapons -- Fiction; Humorous stories; JUVENILE FICTION / Comics & Graphic Novels / General; JUVENILE FICTION / Action & Adventure / Survival Stories; JUVENILE FICTION / Humorous Stories; Monsters; Supervillains; Survival; Weapons; Zombies; Winter -- Fiction; Monsters -- Fiction; Supervillains -- Fiction; Weapons -- Fiction; Children's stories; Horror fiction; Humorous fiction; Fiction; Horror fiction; Humorous fiction; Juvenile works; Humorous fiction; Horror fiction; Humorous fiction